The Effectiveness of Laughter Yoga Training on Quality of sleep and positive and negative affect of female teachers with diabetes - Heidari, Elahe; Shirazi, Mahmoud; Sanaguye Moharer, Gholam Reza (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this study was to determine the effectiveness of laughter yoga training on sleep quality and positive and negative affect of female teachers with diabetes. Method: The research method was quasi-experimental with two groups of experimental and control, pre-test, post-test and two-month follow-up and the statistical population was 70 female teachers with diabetes in Zahedan in 1397. Sixty women were selected from this community in an accessible manner and randomly assigned 30 individuals in each of the experimental and control groups. The research tools were Pittsburgh Sleep Quality Questionnaire (1989) and Watson, Clark & Telgene (1988) Positive and Negative Affect Scale and Medical Laughter Yoga Program (2011) in 8 sessions of 60 sessions of two sessions per week for the experimental group. Data were analyzed using repeated measures analysis of variance. Results: Results showed the effect of laughter yoga training on sleep adequacy (F = 4.15, P = 0.046), positive affect (F = 12.16, P = 0.001), and negative affect (F = 14.64, P = 0/001) and stability of this effect was at follow-up.Conclusion: According to the findings of this study, laughter yoga training can be used as a complementary treatment along with other therapies to improve sleep quality and positive affect and reduce negative affect in women with diabetes.